Evidence of deterministic assembly according to flowering time in an old‐field plant community. (4th February 2013) - Dante, Sneha K.; Schamp, Brandon S.; Aarssen, Lonnie W.; Knapp, Alan
Summary Theory has produced contrasting predictions related to flowering time overlap among coexisting plant species largely because of the diversity of potential influences on flowering time. In this study, we use a trait‐based null modelling approach to test for evidence of deterministic assembly of species according to flowering time in an old‐field plant community. Plant species coexisting in one‐metre‐square plots overlapped in flowering time significantly more than expected. This flowering synchrony was more pronounced when analyses focused on bee‐pollinated species. Flowering synchrony was also observed for wind‐pollinated species, although for only one of our two null model tests, highlighting the sensitivity of some results to different randomization methods. In general, these patterns suggest that relationships between pollinators and plants can influence community assembly processes. Because our study community is composed of approximately 43% native plant species and 57% exotic species, and because the arrival of new species may complicate plant–pollinator interactions, we tested whether flowering time overlap was altered by introduced species. Flowering synchrony was greater in plots with a higher proportion of introduced species. This pattern held for both null model tests, but was slightly stronger when analyses focused on bee‐pollinated species. These results indicate that introduced species alter community flowering distributions and in so doing will inevitably affect pollinator–plant interactions. Finally, we tested whether our results were influenced by variation among study plots in above‐ground biomass production, which some theory predicts will be related to the importance of competition. Our results were not influenced by this variation, suggesting that resource variation among our plots did not contribute to observed patterns. Synthesis: Our results provide support for predictions that coexisting species should display flowering synchrony, and provide no support for species coexistence via temporal niche partitioning at this scale in this study community. Our results also indicate that introduced species significantly alter the community assembly process such that flowering synchrony is more pronounced in plots with a greater proportion of introduced plant species.